Acute endocrine, immune, and muscle damage responses following a 2,000-m rowing time trial in elite male athletes - Ha, Soo-Min; Ha, Min-Seong; Lee, Minchul (Frontiers in Physiology, 2025)
BackgroundRowing is a whole-body sport characterized by high-intensity efforts that require simultaneous aerobic and anaerobic energy provision. Although endurance physiology is well documented, the acute systemic responses to competitive rowing remain insufficiently understood. The present study examined endocrine stress responses, leukocyte redistribution, and muscle damage dynamics following a 2,000-m rowing time trial in elite male athletes.MethodsTwenty national-level rowers (age: 20.4 ± 1.2 years; height: 180.0 ± 4.3 cm; body mass: 80.6 ± 8.7 kg) completed a standardized 2,000-m ergometer test. Venous blood samples were collected at baseline (PRE), immediately post-exercise (POST), and 30 min after exercise cessation (REC30). Serum cortisol was quantified by radioimmunoassay, plasma catecholamines by high-performance liquid chromatography, leukocyte subpopulations by flow cytometry, and muscle damage markers (creatine kinase [CK], lactate dehydrogenase [LDH]) by enzymatic analysis. Normality was evaluated, and repeated-measures ANOVA or Friedman tests were applied with Bonferroni-adjusted post-hoc comparisons.ResultsMean performance time was 6:49.6 ± 14.7 min, corresponding to a mean power output of 328.4 ± 34.1 W. Cortisol, epinephrine, and norepinephrine increased markedly at POST (p < 0.001) and remained elevated at REC30. Total white blood cells, neutrophils, monocytes, eosinophils, and basophils peaked at POST and declined toward baseline by REC30. Lymphocytes rose at POST but decreased below baseline at REC30 (p < 0.001), and the neutrophil-to-lymphocyte ratio exhibited a biphasic pattern. CK and LDH increased acutely at POST and partially regressed at REC30, remaining above baseline.DiscussionThese findings indicate that maximal rowing performance elicits pronounced endocrine activation, transient immune redistribution, and acute muscle damage. Tailored recovery strategies may be necessary to counteract immune suppression and support sustained performance in elite rowers.